Exogenous Proline and Glycine Betaine Mediated Upregulation of Antioxidant Defense and Glyoxalase Systems Provides Better Protection against Salt-Induced Oxidative Stress in Two Rice (Oryza sativa L.) Varieties - Hasanuzzaman, Mirza (Hindawi Publishing Corporation, 2014)
The present study investigates the roles of exogenous proline (Pro, 5 mM) and glycine betaine (GB, 5 mM) in improving salt stress tolerance in salt sensitive (BRRI dhan49) and salt tolerant (BRRI dhan54) rice (Oryza sativa L.) varieties. Salt stresses (150 and 300 mM NaCl for 48 h) significantly reduced leaf relative water (RWC) and chlorophyll (chl) content and increased endogenous Pro and increased lipid peroxidation and H(2)O(2) levels. Ascorbate (AsA), glutathione (GSH) and GSH/GSSG, ascorbate peroxidae (APX), monodehydroascorbate reductase (MDHAR), dehydroascorbate reductase (DHAR), glutathione reductase (GR), glutathione peroxidase (GPX), catalase (CAT), and glyoxalase I (Gly I) activities were reduced in sensitive variety and these were increased in tolerant variety due to salt stress. The glyoxalase II (Gly II), glutathione S-transferase (GST), and superoxide dismutase (SOD) activities were increased in both cultivars by salt stress. Exogenous Pro and GB application with salt stress improved physiological parameters and reduced oxidative damage in both cultivars where BRRI dhan54 showed better tolerance. The result suggests that exogenous application of Pro and GB increased rice seedlings' tolerance to salt-induced oxidative damage by upregulating their antioxidant defense system where these protectants rendered better performance to BRRI dhan54 and Pro can be considered as better protectant than GB.